A Review of Traditional Vaccine-Preventable Diseases and the Potential Impact on the Otolaryngologist - Greenlee, Christopher J.; Newton, Stephen S. (International Archives of Otorhinolaryngology, 2018)
Introduction A majority of otolaryngologists have not had direct experience with many vaccine-preventable diseases since the creation of national vaccination programs. Despite the elimination of endemic transmission of some of these diseases in the United States, outbreaks can occur anywhere and still pose a threat to public health around the world. Recent outbreaks and changing trends in exemption rates indicate that it is important for physicians to maintain a working knowledge of how these diseases present and of the recommended treatment guidelines.Objectives This review will evaluate the current state of vaccination rates, vaccine exemption rates and disease incidence in the United States and in the world. It will also examine the clinical presentation and treatment recommendations of these diseases.Data Synthesis United States estimated vaccination rates, vaccine exemption rates and vaccine-preventable disease incidences were obtained from data compiled by the Centers for Disease Control and Prevention. World vaccination rates and disease incidences were obtained from the World Health Organization databases, which compile official figures reported by member states. A PubMed literature review provided information on the current state of vaccination exemptions and outbreaks in the United States.Conclusion Vaccination and vaccine exemption rates continue to put the United States and many areas of the world at risk for outbreaks of vaccine-preventable diseases. Clinical guidelines should be reviewed in the event of a local outbreak.
Keywords: vaccine; otolaryngology; public health; disease outbreaks; disease eradication; vaccination